The AUP on Nicaragua - Sequeira Ortiz, Deyanira (1983)
In 1972 an earthquake destroys the principal libraries of Nicaragua and during the insurrection in 1979 they were plundered or destroyed other. The great crusade of Literacy in 1980, was it firstly revolutionary task, produced an increase in the reading population of 400.000 persons in only one year. How to attend to the ancient users and to this new avalanche that came to the educational centers with one grapevines suppressed for forty years of dictatorship?